STUDI KOMPARATIF PELAKSANAAN PERADILAN ISLAM DI NEGARA MALAYSIA DAN SAUDI ARABIA - Yusrizal yusrizal (DE LEGA LATA: JURNAL ILMU HUKUM, 2017)
The legal system in Malaysia State reflects the plural model which appears in English Malay Colony. Much of the area of life must be governed by a federal public body. The shariah Court in Malaysia known as the Shariah Court which is a judicial institution that speaks, and sentences to Muslims for civil and criminal misconduct according to the jurisdiction allocated to it. The Shariah Court has jurisdiction as stipulated by the Malaysian Constitution. While in Saudi Arabia Quran and Sunnah Rasulullah s.a.w is the Constitution of the State, and shariah as the basic law implemented by tribunals (courts) shariyah with ulama as Judges and counselors. The Saudi Arabia judiciary is formed based on Islamic shariah which is inseparable from the role of King Abdul Aziz bin Abdul Rahman as-Saud who plundered the territories.